2015
DOI: 10.1002/btpr.2094
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of viral filtration performance of monoclonal antibodies based on biophysical properties of feed

Abstract: Controlling viral contamination is an important issue in the process development of monoclonal antibodies (MAbs) produced from mammalian cell lines. Virus filtration (VF) has been demonstrated to be a robust and effective clearance step which can provide ≥4 logs of reduction via size exclusion. The minimization of VF area by increasing flux and filter loading is critical to achieving cost targets as VFs are single use and often represent up to 10% of total purification costs. The research presented in this pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 23 publications
4
32
0
Order By: Relevance
“…Previous studies (Bakhshayeshi & Zydney, 2008; G. R. Bolton, Spector, & LaCasse, 2006;Dishari et al, 2015;Hongo-Hirasaki, Komuro, & Ide, 2010;Rayfield et al, 2015;Wickramasinghe, Stump, Grzenia, Husson, & Pellegrino, 2010) show that buffer conditions, including pH, buffer type, and ionic strength could affect the filtration performance of the virus filters. In addition, earlier studies have shown that the performance of virus filters is also dependent on the specific protein in the feed (Stuckey et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (Bakhshayeshi & Zydney, 2008; G. R. Bolton, Spector, & LaCasse, 2006;Dishari et al, 2015;Hongo-Hirasaki, Komuro, & Ide, 2010;Rayfield et al, 2015;Wickramasinghe, Stump, Grzenia, Husson, & Pellegrino, 2010) show that buffer conditions, including pH, buffer type, and ionic strength could affect the filtration performance of the virus filters. In addition, earlier studies have shown that the performance of virus filters is also dependent on the specific protein in the feed (Stuckey et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have investigated the effect of pH and types of fouling species on the virus filter capacity and proposed various strategies such as using adsorptive prefilters to achieve higher throughput (Bakhshayeshi & Zydney, 2008; G. R. Dishari et al, 2015;Hongo-Hirasaki et al, 2010;Wickramasinghe et al, 2010). Previous work (Rayfield et al, 2015) also examined the correlation between the biophysical properties and the virus filtration performance and found that molecular size determined by absolute size-exclusion chromatography is an important factor. Previous work (Rayfield et al, 2015) also examined the correlation between the biophysical properties and the virus filtration performance and found that molecular size determined by absolute size-exclusion chromatography is an important factor.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriophages, endogenous CHO Type C retrovirus‐like particles (RVLPs), and biologic feedstreams have been used in attempts to economically predict the outcomes of viral clearance studies . However, due to the differences in physicochemical characteristics of bacteriophage models and the complexities involved in producing purified and highly concentrated RVLP spiking stocks, the scope of utility for these surrogates have remained narrow.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that virus breakthrough can occur with small virus retentive filters during long processing times . However, proper evaluation and control of process parameters and solution properties can maintain high filter flux and mitigate this risk . These findings suggest that when an operating space is determined, within which there is sufficient clearance of small virus to assure patient safety, it may be generically applied to larger virus across multiple products.…”
Section: Scientific and Technology Considerationsmentioning
confidence: 99%